Prarancangan Pabrik Sodium Dodekilbenzena SulfonatDari Dodekilbenzena Dan Oleum 20%Kapasitas Produksi 45.000 Ton/Tahun - Prakoso, Wisnu Subarkah Adi; , Ir. Nur Hidayati, M.T.. ph.D (2017)
ABSTRACT Plant of Sodium dodecylbenzene sulfonates with the raw materials of dodecyilbenzene and oleum 20%, with capacity of 45,000 tons a year is planned for 330 days a year operation. The plant will be established in Cilegon, Banten, takes acres 11,600 m2 and the number of employees who will be needed is 100 people. The process of making sodium dodecyllbenzene sulfonates performed in the continous stirred tank reactor by way of reacting dodecylbenzene and 20% oleum. In the continous stirred tank reactor, reaction that takes place is a liquid phase, on the constant operating temperature of 46 ° C and a pressure of 1 atm. Produce sodium dodecylbenzene sulfonates for 3,681.513 kg per hour,20% Oleum 4,537.465 kg per hour, and 645.06 kg per hour NaOH Product sodium dodekilbenzene sulfonat as 8.430,44 kg per hours. Supporting utilities production process includes provision of water comes from the river of 44.372,46 ton per year, needs 161.342 kg of steam per hour, with diesel fuel of 11.969 liter per years, power and provision of PLN and generator of 120,50 kW. Plant of sodium dodecylbenzene sulfonates's plant is amount to Rp. 795.236.197.387 .30. From economic analysis, the profit before tax is Rp 138.602.458.568,81 per year and a profit after tax of 30% amounting to Rp. 97.021.720.998 General per year. Percent return on investment (ROI) before tax is 33.93% and after tax is 23,75%. Pay out time (POT) before tax is 2.27% per year and after tax is 2.96% per years. Break even point (BEP) is 49.99% and Shut down point (SDP) is 28,02%. Internal Rate of Return (IRR) calculate for 37,20%. Based on the data above, the plant of sodium dodecylbenzene sulfonates from 20% oleum is possible to set up. Keywords : Sodium dodecylbenzene sulfonates, sulfonation, continous stirred tank reactor